Crosstalk between stromal, immune, and ovarian cancer cells in lipid-rich tumor microenvironment exhibits proliferative features - Ma, Qinsiyu; Kang, Rui; Xu, Ruiyue; Guan, Yifu; Chang, Shijie; Li, Shuo (Frontiers in Immunology, 2025)
Lipid metabolism reprogramming has long been noticed as the hallmark of ovarian cancer, in order to maintain proliferative features including rapid cell division, metastasis capability, and chemotherapy resistance, as well as to survive under environmental stress, alteration of lipid metabolic pathways takes place, especially over-expression of rate-limiting enzymes, enhances lipid uptake, fatty acid synthesis, β-oxidation, lipid storage, and cellular membrane construction. In lipid-rich ascites and omental tumor microenvironments, the biological functions of stromal and immune cells change, forming a premetastatic niche and immunosuppressive tumor microenvironment via modifying extracellular matrix components and secreting cytokines. The crosstalk between stromal, immune, and ovarian cancer cells results in tumor proliferation, metastasis, and escape of immune surveillance. Given the importance of lipid metabolism for ovarian cancer survival, targeting lipid metabolism key enzymes in ovarian cancer or stromal tumor microenvironment may bring novel insights for ovarian cancer treatment.